PROTES SOSIAL DALAM KUMPULAN CERITA PENDEK MATI BAIK-BAIK, KAWAN KARYA MARTIN ALEIDA: PENDEKATAN SOSIOLOGI SASTRA - Risda Nur Widia; Widowati Widowati (Universitas Sarjanawiyata Tamansiswa, 2015)
This aims of the paper are to describe and explain things as follows. (1) The plot in a collection of short stories Good Die, man. (2) People and Personalities in the short story collection Mati Baik-Baik, Kawan. (3) Setting the story in a collection of short stories Mati Baik-Baik, Kawan. (4) Social protests in the collection of short stories Mati BaikBaik, Kawan.Â This research is a qualitative description of the research. This research data is qualitative data in the form of sentences/paragraphs in units of events. The data are obtained from the entire text of The Good Die short story collection, Comrade in which there is an idea of the form of characters, settings, and description of the types of social criticism to be based on facts and data. Instruments in this study are the researchers themselves are equipped with sets of theories concerning the sociology of the literature. Data collection method used the method of literature, while the technique of data collection techniques used to read and record the techniques. Methods of the data analysis used in this research are analysis of the content, while the technique of data analysis in this research is descriptive qualitative. The research of the study is as follows. (1) Determine the flow in the short story collection Mati Baik-Baik, Kawan is a chronological flow. (2) Figures in the short story collection Mati Baik-Baik, Kawan, Comrade each consisting of two to two characters with a simple gesture. (3) Setting the story in the collection of short stories Mati BaikBaik, Kawan is in big cities with the social conditions of the lower middle class in 1965. (4) social protests are divided into three areas: the political, cultural, economic and then described in more detail, namely protest to the government and society.Â